Varietal resistance of pea to powdery mildew in dry temperate zone of Himachal Pradesh - and R.S. JAMWAL, B.R. THAKUR, A.S. KAPOOR (Indian Phytopathology, 2002)
In 1992-93 pea lines were tested for resistance to powdery mildew disease caused by Erysiphe pisi in Himachal Pradesh, India. Of 86 lines tested, 7 had a disease score of <10% and were categorised as resistant. These were Sugar Giant, Pant P-8, DPP-54, PMR-3, JP-71, DPP-26 and HPPC-95. Another 14 lines were moderately resistant (<25% infection) which included Rachana, previously found to be resistant. It is concluded that the resistant lines could be used in breeding programmes for developing disease resistant varieties.